2019
DOI: 10.1111/febs.14739
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the role of endoplasmic reticulum stress in skin function and associated diseases

Abstract: Endoplasmic reticulum (ER) stress is a mechanism that allows to protect normal cellular functions in response to both internal perturbations, such as accumulation of unfolded proteins, and external perturbations, for example redox stress, UVB irradiation, and infection. A hallmark of ER stress is the accumulation of misfolded and unfolded proteins. Physiological levels of ER stress trigger the unfolded protein response (UPR) which is required to restore normal ER functions. However, the UPR can also initiate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 81 publications
1
52
0
Order By: Relevance
“…They explain how communication between the UPR and microbe‐sensing pathways can amplify cytokine production. This informs the discussions in several other articles of this Special Issue, including the review by Yoshikazu Uchida and colleagues on inflammatory skin conditions .…”
supporting
confidence: 56%
“…They explain how communication between the UPR and microbe‐sensing pathways can amplify cytokine production. This informs the discussions in several other articles of this Special Issue, including the review by Yoshikazu Uchida and colleagues on inflammatory skin conditions .…”
supporting
confidence: 56%
“…Emerging evidence has suggested that pharmacological targeting of ER stress can be an effective therapeutic strategy for treating tumors (34)(35)(36). Different natural compounds induced ER stress-mediated death in cancer cells (37). ER stress was also identified to serve a critical role in the pathogenesis of vitiligo (38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…The transcription factor is constitutively expressed in all tissues [34]. Nrf2 functions at the interface of cellular redox and intermediary metabolism reactions as the target genes are involved in antioxidant enzyme production [3537]. Nrf2 is a basic region leucine zipper transcription factor [38] that forms heterodimers in the nucleus of cells which recognises the enhancer sequence known as antioxidant response element (ARE).…”
Section: Oxidative Stressmentioning
confidence: 99%